Incidence of Bacterial Infections Following Elective Endoscopic Variceal Ligation of Cirrhotic Patients in a Tertiary Care Hospital - Bashar, Khondaker Abul; Rowshon, A H M; Ghosh, Dilip Kumar; Ahmed, Habib; Sarkar, Debashis Kumar; Ullah, Parash; Chowdhury, Samsuddin Al Masud (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Esophageal varices are the consequence of portal hypertension which occurs mostly due to chronic liver disease and bleeding from rupture of this is one of the modes of death. Endoscopic variceal ligation (EVL) till date is recommended and most accepted method of treatment for prevention of both acute and chronic variceal bleeding of cirrhotic patients. Cirrhotic patients are vulnerable to have infection and it is expected to be augmented by any kind of intervention. Endoscopic variceal ligation being used as a modality of treatment, have the potentiality to cause infection in cirrhotic patients and empirical antibiotic prophylaxis is widely practiced in elective EVL but data regarding this is scanty and hence this study was undertaken in the Dept of Gastroenterology from January,2019 to December, 2019. Aims: To see the incidence of bacterial infection in cirrhotic patients following elective EVL. Methods: Fifty four patients were enrolled fulfilling the inclusion and exclusion criteria. Clinical evaluation and biochemical parameters including CBC, CRP, Blood culture, serum billirubin, serum albumin and PT were done. Fifty four EVL sessions were done and in each session, two to six bands were applied. Patients were followed up for 24 hrs to see any clinical signs of infection and CBC, CRP, Blood culture were done at 24 hrs of EVL. Results: Among fifty four subjects, male were 39(72.2%), and female were 15(27.8%) with mean age 46.62 ± 1.34. Eight patients were in Child Pugh A, 43 in Child B and 3 in Child C class ( Child Pugh classification is used to see prognosis in Cirrhosis comprising Encephalopathy, serum billirubin, serum albumin, PT and ascites) . Hepatitis B virus was found to be the most common etiology. Only one subject of Child B class had neutrophilllic leukocytosis with normal other parameters of infection. All other patients did not show any features of infection both clinically and biochemically. Conclusions: The incidence of bacterial infection was found to be an uncommon event following elective EVL in this study J Shaheed Suhrawardy Med Coll 2021; 13(2): 113-116